International Railway Journal and Rapid Transit Review : IRJ (Rotterdam Simmons-Boardman Pub. Corp.)
Signatura: E 38/14
Existencia: 1976- nov.; 1977- jul.; 1979- ene.-oct., dic.
Keywords: Ferrocarriles